THE INFLUENCE OF PERCEPTION OF PRICE, FACILITIES, AND SERVICE QUALITY ON MEMBER SATISFACTION OF ALL HAPPY GYM FITNESS CENTER BRANCHES IN THE ERA OF GLOBAL DISRUPTION - Soetijono, Audrey Shannen; Wiryakusuma, I Gusti Bagus Yosia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research seeks to examine how price perception, amenities, and service quality impact satisfaction of Happy Gym Fitness Center members in all East Java branches. This research employs a quantitative methodology. with the explanatory research method, where primary data is obtained through a questionnaire distributed to 320 active member respondents. SPSS software was used to analyze the data. The results of the study show that simultaneously the perception of price, facilities, and service quality affect customer satisfaction. However, only partially facilities and service quality have a significant effect, while price perception has no effect on customer satisfaction. These findings indicate that in the context of fitness centers, customer satisfaction is more influenced by non-price aspects, especially the quality of facilities and services. This research makes a practical contribution to Happy Gym's management in formulating strategies to increase customer satisfaction and loyalty through facility improvement and service quality improvement, while strengthening competitiveness in the increasingly competitive fitness industry. The implications of these findings show that a focus on excellent service and modern facilities is a key factor in building a memorable and sustainable customer experience.